2017
DOI: 10.3390/nu9091011
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ and Children’s Salt Taste Perception and Liking: A Review

Abstract: Sodium is an essential nutrient for the human body. It is widely used as sodium chloride (table salt) in (processed) foods and overconsumed by both children and adults, placing them at risk for adverse health effects such as high blood pressure and cardiovascular diseases. The current review focusses on the development of salt taste sensitivity and preferences, and its association with food intake. Three -to- four month old infants are able to detect and prefer sodium chloride solutions over plain water, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 98 publications
0
53
0
3
Order By: Relevance
“…Sugar and sodium have an important function in food processing, affecting the sensory characteristics and shelf-life of a product, 60,61 particularly making food more palatable. 62,63 Given that children demonstrate a preference for sweet 64,65 and salty 66,67 food, these outcomes may reflect manufacturing strategies to increase product sales. In contrast to our findings, Louie et al 68 found that cereals displaying an alternative labelling system, the DIG, had significantly higher sugar content than those without the DIG.…”
Section: Discussionmentioning
confidence: 99%
“…Sugar and sodium have an important function in food processing, affecting the sensory characteristics and shelf-life of a product, 60,61 particularly making food more palatable. 62,63 Given that children demonstrate a preference for sweet 64,65 and salty 66,67 food, these outcomes may reflect manufacturing strategies to increase product sales. In contrast to our findings, Louie et al 68 found that cereals displaying an alternative labelling system, the DIG, had significantly higher sugar content than those without the DIG.…”
Section: Discussionmentioning
confidence: 99%
“…Term Born Infants At birth, infants show an aversion or indifference to salty solutions in contrast to plain water [18][19][20][21]. According to Liem [21], the preference for salty taste develops because of repeated exposure to salty foods [21].…”
Section: Human Studiesmentioning
confidence: 99%
“…Both, genetic predisposition and learned experience from environment influence children's preferences to salt. The review study [64] states that although the liking of salty food starts as unlearned response in early infancy, this liking soon develops as a result of repeated exposure to salty food. Generally speaking, a low exposure to salty food in infancy is associated with low preference for salty food [64].…”
Section: Development Of Adequate Dietary Habits In Early Childhoodmentioning
confidence: 99%
“…The review study [64] states that although the liking of salty food starts as unlearned response in early infancy, this liking soon develops as a result of repeated exposure to salty food. Generally speaking, a low exposure to salty food in infancy is associated with low preference for salty food [64]. No study suggested that decreasing the exposure to salt during infancy is associated with an increased liking of desire for salty foods.…”
Section: Development Of Adequate Dietary Habits In Early Childhoodmentioning
confidence: 99%
See 1 more Smart Citation